Australia's national climate: learning to adapt?. (31st July 2017) - Rickards, Lauren; Neale, Timothy; Kearnes, Matthew
Abstract: Pride in Australia's extreme climate has long been a part of Australia's national identity. Today, climate continues to be enrolled in a range of nationalistic projects, including the (re)development of climate science and other responses to climate change. In this paper, we outline some of the contours of the 'Australian national climate', claims to know it, and four idealised responses to it: bounce back, dismissal, endurance, and migration. We argue that the deeply cultural framing of climate in Australia—in particular, Australians' emphasis on the climate's inherent variability and unknowability, and their own historical adaptability—is being exploited by the federal government and hampering climate change mitigation nationally.